Primary parotid gland lymphoma: pitfalls in the use of ultrasound imaging by a great pretender - Mantsopoulos, Konstantinos; Koch, M.; Fauck, Vanessa; Schinz, Katharina; Schapher, Mirco; Constantinidis, J.; Rösler, Wolf; Iro, Heinrich (International journal of oral and maxillofacial surgery, 2020)
The aim of this study was to highlight several misleading imaging and clinical aspects of parotid gland lymphoma, taking our personal experience and relevant literature reports into consideration. The records of all patients diagnosed with lymphoma in the parotid gland between 2005 and 2017 were examined retrospectively. Sixty-seven patients were included in this study. The mean age was 61.4 years. The most frequent histological entities were marginal zone B-cell lymphoma (31.3%) and follicular lymphoma (28.4%). The tumour was stage I in 35 cases (52.2%), stage II in 13 cases (19.4%), stage III in 11 cases (16.4%), and stage IV in eight cases (11.9%). B symptoms were seen in only three patients (4.5%). The diagnosis was made after parotidectomy in 51 cases (76.1%), by core needle biopsy in 14 cases (20.9%), and by means of open biopsy in the remaining two cases (3.0%). Parotid gland lymphoma represents a diagnostically challenging, multifaceted entity that can easily mimic both benign and malignant conditions. This entity should be included in the differential diagnosis of almost all types of parotid lesion, as it seems to play the role of a great pretender.
CRIS-Team Scopus Importer:2021-04-19
Keywords: diffuse large B-cell lymphoma; follicular lymphoma; lymphoma; MALT lymphoma; marginal zone B-cell lymphoma; parotid gland; parotidectomy; ultrasound